2021
DOI: 10.1016/j.est.2021.102950
|View full text |Cite
|
Sign up to set email alerts
|

On-line state of charge estimation of embedded metal hydride hydrogen storage tank based on state classification

Abstract: With the further deterioration of environment and the depletion of fossil fuels, the alternative energy sources are urgently needed to be discovered. Hydrogen holds great promise thanks to its unlimited resources, high energy density and the environmentally friendly nature. However, its low volume density under normal temperature and pressure becomes the main challenge for on-board storage.Owing to its high potential of safety, one of the optimal solution for the future hydrogen vehicle is storing hydrogen usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, metal hydrides can densely store hydrogen in moderate temperature and pressure conditions 1 , 13 , 19 . Metal hydride materials have some essential features such as fast hydrogen absorption and desorption kinetics, the ability to tolerate poisonous materials and contaminations in the hydrogen feedstock, produced efficiently with minimum cost, easy activation, and stability 16 , 20 – 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, metal hydrides can densely store hydrogen in moderate temperature and pressure conditions 1 , 13 , 19 . Metal hydride materials have some essential features such as fast hydrogen absorption and desorption kinetics, the ability to tolerate poisonous materials and contaminations in the hydrogen feedstock, produced efficiently with minimum cost, easy activation, and stability 16 , 20 – 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Metal Hydrides are classified into elemental, intermetallic, and complex hydrides 14 . The commonly used hydrogen-storing hydrides are classified based on their stoichiometries; They include but are not limited to AB 5 -type, AB 2 -type, A 2 B-type, and AB-type 7 , 14 , 20 . In these structures, A and B are metals with high and low affinity for hydrogen, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen generation, consumption and storage system where an electrolyzer can be used to obtain hydrogen from water, a fuel cell that will generate electrical and thermal energy and a hydrogen tank to store hydrogen [12]. Zhu, D et al investigated the state of charge (SOC) estimation of embedded MH hydrogen storage tanks, designed a joint multiclassifier to identify the current state of the hydrogen reaction, and indicated that at ambient temperature and pressure, metal hydride ( MH) storage of hydrogen is one of the best solutions for future hydrogen-fueled vehicles [13]. Apostolou, D. found that metal hydride storage has an advantage in the price of dispensing hydrogen fuel and is expected to be a primary means of storing hydrogen for small hydrogen-fueled vehicles through a comparison between metal hydride storage devices and compressed hydrogen storage tanks [14].…”
Section: Introductionmentioning
confidence: 99%